Pulmonary coin lesion caused by Dirofilaria immitis – a report of two cases with a minireview of the literature - Jerše, Maja (Polish Journal of Pathology, 2022)
Dirofilariasis is a rare zoonosis, transmitted from infested dogs or other carnivorous animals to humans via mosquitoes. Two male patients with a solitary, peripheral, well-defined, coin-like pulmonary lesion in the right upper lobe were presented. Rapid enlargement of the lesion within a few months suggested malignancy, resulting in surgical removal. Microscopic examination of the resected lung revealed necrotic circumscribed lesions with embolized parasites in the vessels. Both parasites were females of the species Dirofilaria immitis. They represent the first reported cases of pulmonary dirofilariasis in Slovenia. Awareness of this entity is important in the differential diagnosis of pulmonary coin lesions.